Long-Term Symptomatic and Functional Remission with Paliperidone Palmitate 6-Monthly Treatment in Schizophrenia: A 3-Year Post-Hoc Analysis - Hamilton JM; Johnston KL; Simples Jnr J; Turkoz I; Lim L; Antunes J; Obando C; Mattingly G (Neuropsychiatric Disease and Treatment)
Joshua M Hamilton,1 Karen L Johnston,2 James Simples Jnr,2 Ibrahim Turkoz,2 Lisa Lim,2 Jose Antunes,3 Camilo Obando,2 Gregory Mattingly4 1Washington State University, College of Nursing, Department of Advanced Practice & Community-Based Care, Spokane, WA, USA; 2Johnson & Johnson, Titusville, NJ, USA; 3Johnson & Johnson, Porto Salvo, Portugal; 4St. Charles Psychiatric Associates, St. Charles, MO, USACorrespondence: Karen L Johnston, Johnson & Johnson, 1125 Trenton-Harbourton Road, Titusville, NJ, 08560, Email KJohns33@its.jnj.comPurpose: Long-acting injectable (LAI) formulations of paliperidone palmitate (PP) 1-month-(PP1M), 3-month-(PP3M), and 6-month-(PP6M) have been shown to delay time to relapse and to lower relapse rates, while maintaining symptomatic and functional improvements in patients with schizophrenia. This post-hoc analysis assessed symptomatic and functional remission rates in patients who transitioned from PP3M to PP6M (PP3M/PP6M) or continued PP6M (PP6M/PP6M) over 3 years.Methods: Adult patients with schizophrenia, clinically stable on moderate/high doses of PP1M or PP3M, were randomized to PP6M or PP3M during the 12-month double-blind (DB) phase of a phase-3, noninferiority trial (NCT03345342). Eligible patients who remained relapse-free at the end of the noninferiority trial could choose to continue PP6M in a 2-year, single-arm, open-label extension (OLE) study (NCT04072575). Symptomatic remission was assessed using the Andreasen criteria (Positive and Negative Syndrome Scale symptoms [P1,G9,P3,P2,G5,N1,N4,N6] score of ≤ 3 for ≥ 6 months), while functional remission was defined as Personal and Social Performance score > 70.Results: A total of 178 patients either transitioned to PP6M (PP3M/PP6M=57) or continued PP6M (PP6M/PP6M=121) treatment in the OLE study. At the 1-year DB endpoint, 47/57 (82.5%) PP3M/PP6M patients and 103/121 (85.1%) PP6M/PP6M patients achieved symptomatic remission, while 30/57 (52.6%) and 67/121 (55.4%) achieved functional remission, respectively. By the 3-year OLE endpoint, the rates of symptomatic remission (PP3M/PP6M:43/53 [81.1%]; PP6M/PP6M:87/101 [86.1%]) and functional remission (PP3M/PP6M:31/53 [58.5%]; PP6M/PP6M:60/102 [58.8%]) were sustained in both treatment groups. In addition, > 56% of patients who transitioned from PP3M to PP6M or continued PP6M treatment had sustained combined (symptomatic and functional) remission at the OLE endpoint.Conclusion: These findings support the long-term efficacy of PP3M and PP6M, highlighting the potential benefits of transitioning to longer acting antipsychotic formulations in achieving and sustaining both symptomatic stability and functional improvement in adults with schizophrenia.Keywords: functional remission, long-acting injectable antipsychotics, paliperidone palmitate 6-month, schizophrenia, symptomatic remission